A Refractive-Index and Position-Independent Single-Particle Detector for Large, Non-Absorbing, Spherical Particles - Waez, Mir Seliman; Eckels, Steven J.; Sorensen, Christopher M. (My University, 2018)
We show that for spherical particles with real refractive index and diameters greater than ca. 10 microns, the differential scattering cross-section is only independent of the refractive index at angles near 37 ± 5°. We built a device with a modified Gaussian incident beam profile so that the beam transit time of a particle passing through the beam can determine the true incident intensity for the scattering of the particle. By combining the modified Gaussian incident beam profile with detection of scattered light near 37 ± 5°, we demonstrate a refractive-index independent measurement of single spherical particles as they pass through the beam.
Citation: Mir Seliman Waez, Steve J. Eckels & Christopher M. Sorensen (2018) A refractive-index and position-independent single-particle detector for large, nonabsorbing, spherical particles, Aerosol Science and Technology, DOI: 10.1080/02786826.2018.1524133